Action research on E-learning in a Singapore secondary school - Chan, Yin Lai. (2008)
The purpose of this research project is to explore how viable it is to supplement teaching in a Singapore school with e-learning courses and to find out what the main issues and opportunities are which can provide the foundation for changing and improving such courses.